Estrutura etária do rebanho bovino e proximidade da floresta determinando a predação de gado por grandes felinos no Pantanal - Tortato, Fernando Rodrigo (2012)
The conflict caused by large carnivore attacks to livestock constitutes a major threat for the conservation of these species in the world, including the jaguar (Panthera onca) and the puma (Puma concolor) in Brazil. This study has the objective to understand the factors that influence big cat attacks on cattle in a ranch located in the Brazilian Pantanal. Cattle were monitored between January of 2006 and September 2010 and all data regarding cattle mortality was recorded. We measured the economic impact generated by the predation events. We evaluated the influence of the water level of the Paraguai river and the age structure of the cattle herd during attack events by big cats. During the 57 months of monitoring, more than a half of the herd mortality was caused by attacks of large felines causing a maximum annual financial loss of U$$ 22.400,00. In relation to the preference of big cats attacks on cattle herds, it was verified the preference for younger class animals. We found a positive relationship between the frequency of monthly attacks and the water level of the Paraguai river and a negative relationship between monthly attacks and adult proportion of the herd. Based on the data of presence or absence of monthly deaths caused by big cats was observed that the 13 months that the average monthly altimetry Paraguay River exceeded 650 cm, deaths occurred in 12 months. Regarding the proportion of adults in the herd, 73% of deaths caused by attacks of jaguars occurred when the proportion of adults was less than 60% of the herd. Increased altimetry causes a thickening of the herd near forested areas, increasing the vulnerability of it. The influence of the proportion of adults in the herd indicates a defensive behavior by adults. The understanding of these factors that predispose predation events by big cats on cattle herds, contributes for the establishment of management strategies with the aim to reduce these losses.